Identifikasi Modal Sosial pada Sistem Pembiayaan Tanpa Agunan (Studi pada Koperasi Pandawa Kecamatan Sukun Kota Malang) - di, Supar; Manzilati, Asfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this study was to determine how the shape and role of social capital in the form of aÂ trust,Â norm andÂ social networksÂ inÂ finance withoutÂ collateralÂ in Koperasi Pandawa. By using qualitative method with a case study approach, it could be concluded that: (1) the trust is able to createÂ aÂ personalÂ guaranteeÂ thatÂ allowsÂ customersÂ toÂ accessÂ financingÂ inÂ cooperation withÂ the Pandawa materially limited warranty; (2) norm which translates into value together as